2015
DOI: 10.1007/s10620-015-3633-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Ion Channels and Transporters During Hepatocellular Carcinoma Development

Abstract: The ion channel/transporter expression profile observed suggests that these genes are potential early markers or therapeutic targets of HCC. The differential localization of Abcc3 may be useful in the diagnosis of cirrhosis and HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…In the same study, the authors observed that astemizole clearly prevented HCC development in vivo . Another recent finding [ 168 ] reported that several potassium channels were overexpressed in the liver only in the presence of the chemical carcinogen diethylnitrosamine; when the carcinogen treatment finished, the channel mRNA levels returned almost to normal values. The authors suggested that some potassium channels may serve as carcinogen exposure indicators and that gene expression of the Abcc3 transporter may serve as a liver tumor marker.…”
Section: Cancermentioning
confidence: 99%
“…In the same study, the authors observed that astemizole clearly prevented HCC development in vivo . Another recent finding [ 168 ] reported that several potassium channels were overexpressed in the liver only in the presence of the chemical carcinogen diethylnitrosamine; when the carcinogen treatment finished, the channel mRNA levels returned almost to normal values. The authors suggested that some potassium channels may serve as carcinogen exposure indicators and that gene expression of the Abcc3 transporter may serve as a liver tumor marker.…”
Section: Cancermentioning
confidence: 99%
“…The importance of CACNA1H in cancer proliferation has been reported in several recent studies across a variety of cancer types [46], including breast carcinoma, retinoblastoma, neuroblastoma, glioma melanoma, and HCC [46,47]. However, this effect does not appear to depend on changes in CACNA1H expression during HCC development [48].…”
Section: Discussionmentioning
confidence: 99%
“…61 Investigators found that 12 transporters (ABCA2, ABCB1, ABCB6, ABCC1, ABCC2, ABCC3, ABCC4, ABCC5, ABCC10, ABCC11, ABCC12, and ABCE1) were upregulated in HCC compared with healthy liver tissue. 61 Although several studies have demonstrated elevated ABCC3/Abcc3 mRNA expression in HCC liver nodules and tumors, [61][62][63] recently a role of ABCC3 in cancer initiation, promotion, and progression has been proposed. 62 In summary, differences in transporter expression in HCC tissues versus healthy liver tissue have been demonstrated.…”
Section: Hepatic Transporters In Disease Statesmentioning
confidence: 99%